Ökonomische Wirkungen des novellierten Betriebsverfassungsgesetzes: was können wir vor dem Hintergrund zunehmender Globalisierung und veränderter arbeitsorganisatorischer Bedingungen erwarten? - Uwe Jirjahn (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– Against the background of theoretical considerations and available empirical studies, the expected effects of the amendment to the Law on Labour Relations at the Workplace (Betriebsverfassungsgesetz) are discussed. The various basic conditions are shown under which more positive or more negative consequences can be expected for firms' efficiency. Particular attention is paid to the globalisation of the economy, the reorganisation of the world of work and the extent to which firms are bound by collective agreements.
Keywords: 330; Betriebsverfassungsgesetz - Änderung; Mitbestimmung; Mitbestimmungsgesetz; Betriebsrat; Arbeitnehmervertretung; Arbeitnehmerinteresse; Arbeitgebervertretung; Arbeitgeberinteresse; Arbeitsorganisation; organisatorischer Wandel; Dienstleistungsgesellschaft; atypische Beschäftigung; Betriebsgröße; Marktversagen